2022
DOI: 10.15252/embj.2022110833
|View full text |Cite
|
Sign up to set email alerts
|

The MASTL/PP2A cell cycle kinase‐phosphatase module restrains PI3K‐Akt activity in an mTORC1‐dependent manner

Abstract: The AKT‐mTOR pathway is a central regulator of cell growth and metabolism. Upon sustained mTOR activity, AKT activity is attenuated by a feedback loop that restrains upstream signaling. However, how cells control the signals that limit AKT activity is not fully understood. Here, we show that MASTL/Greatwall, a cell cycle kinase that supports mitosis by phosphorylating the PP2A/B55 inhibitors ENSA/ARPP19, inhibits PI3K‐AKT activity by sustaining mTORC1‐ and S6K1‐dependent phosphorylation of IRS1 and GRB10. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Autophagy involves signalling, autophagy movement and vesicle fusion, all related to the PI3K/AKT signalling pathway 8 . AKT activation controls apoptosis, autophagy and development through the phosphorylation of downstream proteins such as mammalian target of rapamycin (mTOR) kinase and forkhead box protein O1 (FOXO1) transcription factor 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy involves signalling, autophagy movement and vesicle fusion, all related to the PI3K/AKT signalling pathway 8 . AKT activation controls apoptosis, autophagy and development through the phosphorylation of downstream proteins such as mammalian target of rapamycin (mTOR) kinase and forkhead box protein O1 (FOXO1) transcription factor 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 AKT activation controls apoptosis, autophagy and development through the phosphorylation of downstream proteins such as mammalian target of rapamycin (mTOR) kinase and forkhead box protein O1 (FOXO1) transcription factor. 9 To explore the involvement of Tp47 in microglial migration and its underlying mechanisms, the impact of Tp47 on autophagy and microglial migration was systematically explored using the human microglial clone 3 (HMC3) cell line in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the calcium and integrin binding protein 2 encoded by the gene CIB2 , which we found here as a negative regulator of NOTCH1, is a negative regulator of mTOR signaling in the mouse retinal pigmented epithelium [80]. Similarly, the MASTL kinase regulates mTOR [81] and EGFR [82]. Finally, as a NOTCH1 modulator we have found MC1R (Melacortin 1 receptor), which in melanocytes contributes to pigmentation by regulating the TFEB paralog MITF, among other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, under nutrient‐poor conditions, TORC1 activity drops and Ppk18 promotes PP2A Pab1 inactivation allowing fast completion of the cell cycle and entry into quiescence in G1 (Chica et al , 2016). Recently, it has been demonstrated that the Greatwall‐ENSA pathway is coupled with nutritional conditions and cell growth in higher eukaryotes as well (Sanz‐Castillo et al , 2023). In fact, during periods of nutrient abundance, mammalian Greatwall kinase is directly activated through phosphorylation by mTORC1.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during periods of nutrient abundance, mammalian Greatwall kinase is directly activated through phosphorylation by mTORC1. This mitosis‐independent activation prevents the activity of PP2A B55 toward downstream targets of mTORC1, thereby contributing to a negative feedback loop in the PI3K/AKT/mTOR pathway (Sanz‐Castillo et al , 2023). Interestingly, in temperature‐stressed budding yeast, the endosulfines were suggested to promote mitotic entry through positive rather than negative regulation of PP2A Cdc55 , possibly by controlling its nucleo‐cytoplasmic distribution (Juanes et al , 2013).…”
Section: Introductionmentioning
confidence: 99%